Pengaruh Kejelasan Anggaran dan Komitmen Organisasi terhadap Kinerja Manajerial ASN dengan Servant Leadership Sebagai Variabel Moderating - Ajeng Wijayanti; Afifah Rahmawati (Jurnal Akuntansi Manajerial, 2022)
This study proves whether the clarity of budget targets and organizational commitment have an influence on the managerial performance of ASN. In addition, it is also to test whether the variables of budget clarity and organizational commitment to the managerial performance of ASN can moderate servant leadership. The population and samples selected in this study were the Parks and Urban Forests Sub-dept. in all areas of DKI Jakarta. The questionnaires which were distributed to the Sub-Department of Parks and Urban Forests in all areas of DKI Jakarta were 50 copies per area, so the total of all copies was 250 copies. The software used is SmartPLS (Partial Least Square). The results of hypothesis testing in this study found that budget target clarity has a positive effect on ASN managerial performance, organizational commitment has a positive effect on ASN managerial performance, the influence of servant leadership on ASN managerial performance has a positive and significant effect, servant leadership weakens the influence of budget target clarity on ASN managerial performance. , servant leadership moderation is not able to strengthen the effect of organizational commitment on the managerial performance of ASN. To prevent such a situation, government agencies should be able to improve servant leadership so as to make ASN have a commitment, because ASN who have a commitment will have optimal performance.